Titania‐Supported Catalysts for Levulinic Acid Hydrogenation: Influence of Support and its Impact on γ‐Valerolactone Yield. Issue 9 (4th May 2015) - Ruppert, A. M.; Grams, J.; Jędrzejczyk , M.; Matras‐Michalska, J.; Keller, N.; Ostojska, K.; Sautet, P.
Abstract Invited for this month's cover are the groups from Lodz University of Technology (Poland), from the University of Strasbourg (France) and from the University of Lyon (France). The image shows, which titania phase can facilitate the Ru metal distribution on its surface and hence which factors thus allow preparing active catalysts for biomass valorization. The Full Paper itself is available at 10.1002/cssc.201403332.